Wellness Management Guided by Voice Input, Featuring an Intelligent AI Health Assistant Named: Raie - Chall, Arpan Kumar; Das, Anapeksha; Jana, Radhakrishna; Mondal, Asmi (International Journal of Computer Sciences and Engineering, 2026)
At the forefront of AI innovation, Rai, an advanced voice assistant, leverages the capabilities of prominent Python libraries. This dynamic fusion of technology, encompassing speech recognition, pyttsx3, pywhatkit, wikipedia, pyjokes, os, and webbrowser libraries, opens the door to limitless possibilities. Rai emerges as a versatile companion, reshaping the digital experience through seamless voice interactions that transcend conventional interfaces. Its diverse array of functions, from orchestrating music playback to extracting information from the internet and providing humor through pyjokes, showcases its versatility. Rai's AI-powered voice interface transforms user interactions, making task execution efficient and empowering. Rai stands as a game-changer, elevating productivity and digital engagement while harmonizing technology with human expression